2021
DOI: 10.3390/agronomy11081674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrification Inhibitors on Soil Nitrification and Ammonia Volatilization in Three Soils with Different pH

Abstract: The application of nitrification inhibitors (NIs) is considered to be an efficient way to delay nitrification, but the effect of NIs combinations on soil nitrification and ammonia (NH3) volatilization are not clear in soils with different pH values. In this study, we explored the effect of nitrapyrin (CP) and its combinations with 3, 4-dimethylepyrazole phosphate (DMPP), dicyandiamide (DCD) on the transformation of nitrogen, potential nitrification rate (PNR), and ammonia (NH3) volatilization in a 120-day incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 58 publications
1
16
1
Order By: Relevance
“…Soil pH has been considered as one of the most important factors controlling NI efficacy, because pH has potential to impact the degradation rate of the NIs in soils. Cui et al (2021) showed that DMPP performed better in alkaline soil compared to acid soil conditions, which may be caused by the shorter half-life time of DMPP in acidic soil compared to alkaline soil. DMPP undergoes degradation in soil through chemical reaction steps, potentially involving reactive oxygen species (ROS) generated through abiotic and/or biotic processes ( Sidhu et al, 2021 ), which would possibly be affected by pH.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Soil pH has been considered as one of the most important factors controlling NI efficacy, because pH has potential to impact the degradation rate of the NIs in soils. Cui et al (2021) showed that DMPP performed better in alkaline soil compared to acid soil conditions, which may be caused by the shorter half-life time of DMPP in acidic soil compared to alkaline soil. DMPP undergoes degradation in soil through chemical reaction steps, potentially involving reactive oxygen species (ROS) generated through abiotic and/or biotic processes ( Sidhu et al, 2021 ), which would possibly be affected by pH.…”
Section: Discussionmentioning
confidence: 97%
“…Soil pH was an important explanatory variable for NI efficacy in reducing N 2 O emissions ( Cui et al, 2021 ). The results from the current meta-analysis showed that NIs had different effects on decreasing N 2 O emissions under different soil pH ( Figure 2A and Table 1 , P < 0.01), and NIs efficacy had a positive response to soil pH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations